2019
DOI: 10.1016/j.ijso.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

To close or not to close? A systematic review and meta-analysis of wound closure in appendicectomy

Abstract: Background/objective: Published studies have shown conflicting results regarding the rate of wound infection between primary and delayed closures in open appendicectomy. This meta-analysis was performed with the aim to summarize all available evidence. Methods: A literature search was carried out using Medline, PubMed, EMBASE and Cochrane databases from inception to January 2018. Randomized controlled studies that compared primary closure (PC) to delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…OR=0.60, 95% CI: 0.23-1.54. 10 Wound infection is an extremely cumbersome morbidity for the patients. It not only increases hospital stay but also leads to poor scar and social burden on patients and their family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OR=0.60, 95% CI: 0.23-1.54. 10 Wound infection is an extremely cumbersome morbidity for the patients. It not only increases hospital stay but also leads to poor scar and social burden on patients and their family.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Several studies and randomized controlled trials (RCTs) have tried to answer this question in the past, with mixed results. 10,11 Meka et al concluded that the risk of SSI in ruptured appendicitis showed no difference between PC and DPC techniques. In low-risk SSI patients, PC does not increase the risk of SSI.…”
Section: Introductionmentioning
confidence: 99%